Microstructure and mechanical properties of armor 500/AISI2205 steel joint by friction welding - Sarsilmaz, Furkan; Kirik, Ihsan; Bati, Serkan (Elsevier Sci Ltd, 2017)
This paper discussed the properties of friction welded joint of Armor 500 steel and duplex (ferritici/austenitic) steel AISI 2205 and compared the properties of weld at different welding parameters. The experimental study was' conducted with the welding parameters such as friction pressure and friction time. The experimental results indicated that armor 500 steel could be joined to AISI 2205 steel using the traditional friction welding technique. The processed joints were tested through axial tension test. In addition, the highest tensile strength, which is 1020 MPa is obtained when friction time is 8s and friction pressure is 80 MPa. The microstructures of the alloys and fracture surfaces were examined by optical and scanning electron microscopy. Experimental results indicate that microstructural and mechanical properties are significantly affected by changing welding parameters within the chosen range of conditions. (C) 2017 Published by Elsevier Ltd on behalf of The Society of Manufacturing Engineers.
Keywords: Friction welding; Armor steel; Duplex stainless